Biomolecular Electron Controller Composed of Nanobiohybrid with Electrically Released Complex for Spatiotemporal Control of Neuronal Differentiation. Issue 2 (16th December 2021) - Lim, Joungpyo; Yoon, Jinho; Shin, Minkyu; Lee, Ki‐Bum; Choi, Jeong‐Woo
Abstract: In vitro spatiotemporal control of cell differentiation is a critical issue in several biomedical fields such as stem cell therapy and regenerative medicine, as it enables the generation of heterogeneous tissue structures similar to those of their native counterparts. However, the simultaneous control of both spatial and temporal cell differentiation poses important challenges, and therefore no previous studies have achieved this goal. Here, the authors develop a cell differentiation biomolecular electron controller ("Biomoletron") composed of recombinant proteins, DNA, Au nanoparticles, peptides, and an electrically released complex with retinoic acid (RA) to spatiotemporally control SH‐SY5Y cell differentiation. RA is only released from the Biomoletron when the complex is electrically stimulated, thus demonstrating the temporal control of SH‐SY5Y cell differentiation. Furthermore, by introducing a patterned Au substrate that allows controlling the area where the Biomoletron is immobilized, spatiotemporal differentiation of the SH‐SY5Y cell is successfully achieved. Therefore, the proposed Biomoletron‐mediated differentiation method provides a promising strategy for spatiotemporal cell differentiation control with applications in regenerative medicine and cell therapy. Abstract : A novel cell differentiation strategy is proposed for spatiotemporal neuronal differentiation using biomolecular electron controller ("Biomoletron"), capable of releasing differentiation‐inducing molecules by electrical stimulation. The Biomoletron adheres and half‐penetrates SH‐SY5Y with biocompatibility. Spatiotemporal control of neuronal differentiation of SH‐SY5Y using the Biomoletron is demonstrated by applying electrical stimulation at specific times and in predetermined regions of the Biomoletron‐immobilized patterned Au substrate.